The role of fiscal policies for external imbalances: Evidence from the European Union - António Afonso; José Carlos Coelho (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
We revisit the relation between budget deficits and current account deficits for 28 European Union countries from 1996 to 2019. We find that an increase in budget deficit of 1 pp of GDP results in a deterioration of the current account deficit of 0.318 pp of GDP, which supports the Twin Deficits Hypothesis. On the other hand, dynamic panel estimates partially corroborate the Equivalence Ricardian Hypothesis in the presence of a fiscal rules index. In addition: i) the relation between the two deficits is asymmetric and the negative impact of the recent Eurozone banking and sovereign debt crisis on the current account balance is observed; ii) after 2010, the budget balance positively affects the current account balance; and iii) the positive impact of the budget balance on the current account balance is higher in the cases of non-Eurozone countries, high budget deficit countries, and low exports countries, whereas it is lower in the cases of Eurozone countries, low budget deficit countries, and high exports countries.
Keywords: F32; F41; H62; C33; 330; budget deficit; external deficit; European Union; fiscal rules; panel data